Kajian antropologi sastra pedagogis pada novel Sokola Rimba karya Butet Manurung - Purwati Anggraini; Suyatno Suyatno; Tengsoe Tjahjono; Joko Widodo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
The research aims to describe (1) the main character's adaptation to orang rimba culture; (2) the main character's steps in providing education to the orang rimba in the "Sokola Rimba" novel. This qualitative research uses the theory of Literary Anthropology and Pedagogy. The data source is Butet Manurung's "Sokola Rimba". The data is in the form of story units containing pedagogical literary anthropology elements. Data collection techniques include reading the object of study accompanied by reading theory, making research indicators and data capture tables, and grouping data into data capture tables. The data analysis technique begins with reducing inappropriate data, describing and interpreting the data, and finally concluding the research results. The results of this study are (1) the adaptation carried out by the main character is understanding the local wisdom of the orang rimba, which includes the orang rimba considering the honey tree as a tree of life, the orang rimba believing in natural signs, the orang rimba having skills in obtaining food and saving themselves, and the naming of places by orang rimba; (2) the main character's steps in providing education to the orang rimba include teaching reading, writing, arithmetic, and communicating while maintaining local wisdom.